Predicting Cervical Lymph Node Metastasis Following Endoscopic Surgery in Superficial Head and Neck Carcinoma - Okabe, Ryuichi; Ueki, Yushi; Ohashi, Riuko; Takeuchi, Manabu; Hashimoto, Satoru; Takahashi, Takeshi; Shodo, Ryusuke; Yamazaki, Keisuke; Matsuyama, Hiroshi; Umezu, Hajime; Terai, Shuji; Ajioka, Yoichi; et al. (Frontiers in Surgery, 2022)
Background: Early detection of head and neck carcinoma (HNC) as superficial HNC (SHNC) identified using recently developed optical techniques, such as magnifying endoscopy and narrow-band imaging (NBI), in combination with endoscopic surgeries enables minimally invasive treatment with favorable outcomes for HNC. This study aimed to identify the predictive factors for the rare but important clinical issue of SHNC, namely cervical lymph node metastasis (CLNM), following endoscopic resection. Methods: Sixty-nine patients with SHNC who underwent endoscopic resection were enrolled in the study. Clinical data, preoperative endoscopic findings, pathological findings, and treatment outcomes were retrospectively reviewed. Because the pharyngeal mucosa lacks the muscularis mucosa, we measured tumor thickness in permanent pathology as an alternative to the depth of invasion. Correlations with the occurrence of CLNM were statistically examined. Results: The 5-year disease-specific survival rate was 100%. Of 69 patients, 3 (4.3%) developed CLNM. All had subepithelial but not epithelial tumors. The 0-IIa type in the macroscopic findings, type B2/B3 vessels in narrow-band imaging, tumors ≥ pathological stage T2, lymphatic invasion, positive surgical margins, and tumor thickness >1000 µm showed significant correlations with CLNM following endoscopic resection. Furthermore, the classification of type B vessels was significantly associated with tumor thickness. Conclusion: The treatment outcomes following endoscopic resection for SHNC were favorable. The risk of CLNM following endoscopic resection in SHNC can be predicted by several preoperative endoscopic and postoperative pathological findings. Among them, the classification of type B vessels, which correlated with both tumor thickness and CLNM, might be a useful predictive factor.